A midline for oxaliplatin infusion: the myth of safety devices. (5th June 2014) - Masters, Ben; Hickish, Tamas; Uña Cidon, Esther
Abstract : Oxaliplatin is a platinum compound mainly used in the treatment of colorectal cancer. According to its manufacturer it is not considered vesicant agent though it has been shown to cause severe tissue damage if extravasation occurs in large doses. Several cases of extravasation have been reported; most of them from incorrectly placed peripheral cannula or incorrect use of central venous access devices. To reduce these risks, peripherally inserted central catheters and midline catheters have been increasingly used and are especially helpful if poor peripheral venous access. Midlines are mainly used for patients not receiving vesicant drugs, and are generally inserted without radiological guidance. They are believed to be safe, but we present the first ever-documented oxaliplatin extravasation injury from a midline catheter.